Papers of Barbara and Richard Appleton - Appleton, Richard, 1932-2005.; Appleton, Barbara, 1941- (1954)
MS 10340 comprises research material, administrative records and reference books used in checking entries relating to the Australian Encyclopaedia (1 box).
Manuscript reference number: MS 10340.
Richard Appleton was trained as a schoolteacher and taught for several years before turning to book editing. In 1972 he became the Production Editor of the The Australian Encyclopaedia, 3rd edition (1977) and Editor-in-Chief of the 4th and 5th editions (1983 and 1988). He later became a member of the Advisory Board and a Chief Contributing Editor of the 6th edition (1996).
Barbara Appleton was a registered nurse and a member of the Blue Mountains Writers Group, where she met Richard. The 5th edition of The Australian Encyclopaedia was edited in and from their home in Petersham, Sydney, and Barbara was an Assistant Editor. Richard and she later wrote The Cambridge Dictionary of Australian Places, Cambridge University Press, 1992.
Keywords: Appleton, Richard, -- 1932-2005 -- Archives; Appleton, Barbara, -- 1941- -- Archives; Australian encyclopaedia; Editors -- Australia -- Archives; Encyclopedias and dictionaries -- Australia; Australia -- Dictionaries and encyclopedias